2001
DOI: 10.1603/0022-2585-38.6.836
|View full text |Cite
|
Sign up to set email alerts
|

Electron Microscopic Observations on Wound-Healing in Larvae of the Mosquito <I>Armigeres subalbatus</I> (Diptera: Culicidae)

Abstract: The wound-healing processes in the mosquito Armigeres subalbatus (Coquillett) were observed with electron microscopy. The initial reaction involved wound contractions and aggregation of injured surface tissues, cell debris and movement of granulocytes toward the wound. Granulocytes first aggregated around the surface of the wound and many filamentous filopodia protruded to connect with cytoplasmic strands. These strands were then interconnected to form a network coagulum resulting in wound closure to prevent b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
22
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 23 publications
1
22
0
Order By: Relevance
“…As summarized earlier, a wound which penetrates the epidermis of an insect results in coagulation, melanisation, cell migration across the melanised clot/scab, and cuticle deposition once the epidermis is made continuous. Much research has been done into the roles played by chemistry (Lai-Fook, 1968;Rowley and Ratcliffe, 1978;Wright, 1987), biology (Wigglesworth, 1937;Locke, 1966;Marmaras et al, 1996;Dillaman and Roer, 1980;Lai et al, 2001) and genetics (Galko and Krasnow, 2004;Belacortu and Paricio, 2011) involved during the wound healing of insects, but how effective are these processes at restoring the original preinjury properties such as strength, stiffness and toughness e crucial for the survival of a limb and the fitness of the insect e to the cuticle? One such study (Parle et al, 2016b) showed that the deposition of a patch of new cuticle underneath a wound is crucial, and can restore the strength of an injured leg to 66% of its original strength.…”
Section: Major Damagementioning
confidence: 99%
See 1 more Smart Citation
“…As summarized earlier, a wound which penetrates the epidermis of an insect results in coagulation, melanisation, cell migration across the melanised clot/scab, and cuticle deposition once the epidermis is made continuous. Much research has been done into the roles played by chemistry (Lai-Fook, 1968;Rowley and Ratcliffe, 1978;Wright, 1987), biology (Wigglesworth, 1937;Locke, 1966;Marmaras et al, 1996;Dillaman and Roer, 1980;Lai et al, 2001) and genetics (Galko and Krasnow, 2004;Belacortu and Paricio, 2011) involved during the wound healing of insects, but how effective are these processes at restoring the original preinjury properties such as strength, stiffness and toughness e crucial for the survival of a limb and the fitness of the insect e to the cuticle? One such study (Parle et al, 2016b) showed that the deposition of a patch of new cuticle underneath a wound is crucial, and can restore the strength of an injured leg to 66% of its original strength.…”
Section: Major Damagementioning
confidence: 99%
“…Also found in this study was that the patch of internal new cuticle deposited to repair the wound was locally Table 2 The four stages of wound healing, their purpose, and what happens, if any one stage is absent. Information gathered from Wigglesworth (1937), Lai-Fook (1966, 1968, Locke (1966), Ratcliffe (1976, 1978), Dillaman and Roer (1980), Wright (1987), Lai et al (2001), Galko and Krasnow (2004), Dushay (2009) and Belacortu and Paricio (2011 targeted to the wound site, and was not due to the effects of normal cuticle growth. That is, the deposition was initiated due to the injury.…”
Section: Major Damagementioning
confidence: 99%
“…Although it has long been suggested that the functions of cuticular POs are for wound healing, defense, and cuticle sclerotization (Lai-Fook, 1966;Brunet, 1980;Ashida and Yamazaki, 1990;Ashida and Brey, 1995;Andersen et al, 1996;Marmaras et al, 1996;Lai et al, 2001), the relative roles of various POs might play in cuticular sclerotization in insect are still debatable. Recently, Arakane et al (2005) demonstrated that another phenol-oxidizing enzyme Laccase 2, play a critical role in sclerotization of the red flour beetle, Tribolium castaneum.…”
Section: Introductionmentioning
confidence: 99%
“…Also, for comparative purposes, intrathoracic injection was the only method by which mosquitoes could be infected with both TE/592J/GFP and MRE16-eGFP because TE/592J/GFP is not infectious per os (Foy et al, 2004;Pierro et al, 2003). However, it should be noted that needle injection elicits a rapid cellular and humoral immune response in mosquitoes (Lai et al, 2001) and is not a natural route of arbovirus infection. Both TE/592J/ GFP and MRE16-eGFP were produced using standard techniques (see Olson et al, 2000) and a volume of 0.5 ml of 1610 8 p.f.u.…”
mentioning
confidence: 99%